The effectiveness of problem – based learning methods in improving high-order thinking skills - Ali, Azita; Islamiah, Doria; Zulkifli, Zuriawahida (2018)
Problem based Learning (PBL) methods is a teaching approach based on real life problems, which involves the utilization of various skills in solving the issue. The purpose of this quasi – experimental research is to study the effectiveness of PBL technique in increasing students’ high order thinking skill. The research took a period of eight weeks to be completed. The instruments used in this research are pre-post test questions and survey. The research involved 71 respondents from Sekolah Menengah Kebangsaan Tun Ismail who were divided into two groups, which are the treatment and controlled groups. All of the respondents were a group of students undertaking the form four Science subject. The acquired data was analysed descriptively and inferentially using the Statistical packages for Social Science Version 21.0 (SPSS) software. The findings of this research have proven that PBL method is successful in increasing students’ high order thinking skill. A similar finding was also obtained regarding students’ perceptions in using PBL to help in their achievements, showing a high mean score of 4.00. In conclusion, the use of PBL shows positive response from students and the findings illustrate that different, interesting and effective teaching and learning methods are more capable of increasing students’ high order thinking skill compared to traditional methods.